1967
DOI: 10.1139/y67-076
|View full text |Cite
|
Sign up to set email alerts
|

Latency of the Gastric Secretory Response to Sham Feeding in the Dog

Abstract: In conscious dogs with gastric fistulas the latency of both the gastric acid and pepsin responses to sham feeding was about 6 min. When a background secretion was induced with various closes of hog gastrin, the latency of the acid response to sham feeding was unchanged, but the latency of the pepsin response was shortened. The peak rates of acid and pepsin secretion after sham feeding were not altered by the infusion of gastrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1974
1974
1974
1974

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…In the present study we failed to demonstrate significant inhibition in vagally innervated fundic pouches. This result confirms the findings in our previous investigation (Wheeler et al, 1973) and that reported by Preshaw (1967); consequently no support is provided for the existence of a neuronal inhibitory mechanism of antral origin active against pentagastrinstimulated acid secretion.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study we failed to demonstrate significant inhibition in vagally innervated fundic pouches. This result confirms the findings in our previous investigation (Wheeler et al, 1973) and that reported by Preshaw (1967); consequently no support is provided for the existence of a neuronal inhibitory mechanism of antral origin active against pentagastrinstimulated acid secretion.…”
Section: Discussionsupporting
confidence: 88%